4.2k views
3 votes
Convert the parametic equation x(L)=2-3t and y(t)=4+L into slope intercept form

1 Answer

7 votes
I guess those 'L' are 't'.

Solve for t in both parametric equations:


x(t) = 2 - 3t \iff t = (x-2)/(-3)


y(t)=4+t \iff t = y-4

Now, you have two expressions for t. The must be equal to each other:


(x-2)/(-3) = y - 4

Solve for y in this last equation:


y = (x-2)/(-3) + 4 = -(1)/(3)x+(14)/(3)

And you've got the slope-intercept form.

Yo could also find from the beginning the slope: it's the quotient of the coefficients of the parameter:


m = (1)/(-3)

And, then find the intercept by plugging the point (2,4) into the equation:


y=-(1)/(3)x+n
User Nick Coelius
by
5.2k points